Students in a Health Crisis: Observations on the Prevention Of Stigmatisation and Exclusion in Polish Higher Education Institutions - Ziółkowska, Agnieszka; Krawiec, Grzegorz (Medicine, Law & Society, 2024)
This study addresses the challenges experienced by students in a health crisis due to stigmatisation and exclusion. The authors of the study, being members of the management personnel of the faculty/institute of law of two different higher education institutions, often witness problems encountered by students on a daily basis. These problems, which affect the course of study and finding one’s way in the academic environment, are not solely linked to didactics or social issues but also encompass health aspects, including issues related to disability and being transgender. For a long time now, we have been observing an increase in the number of students with various types of health problems, which we might interpret as a sign of our times. We are also seeing problems that have become visible only recently (such as the aspect of being transgender, which is a source of feelings of stigmatisation and exclusion). It is becoming necessary for the authorities of higher education institutions to implement multifaceted measures to counteract the phenomenon of stigmatisation and exclusion and provide a sense of security to members of the academic community. The activities and responsibilities set out by the legal system should constitute a certain minimum, which depends on the genuine needs of students.